Saving Time for Patient Care by Optimizing Physician Note Templates: A Pilot Study - Alissa, Rana; Hipp, Jennifer A.; Webb, Kendall (Frontiers in Digital Health, 2022)
Background: At times, electronic medical records (EMRs) have proven to be less than optimal, causing longer hours behind computers, shorter time with patients, suboptimal patient safety, provider dissatisfaction and physician burnout. These concerning healthcare issues can be positively affected by optimizing EMR usability, which in turn would lead to substantial benefits to health care professionals including increased healthcare professional productivity, efficiency, quality and accuracy. Documentation issues, such as non-standardization of the physician note templates and tedious, time-consuming notes in our mother-baby unit (MBU) were discussed during meetings with the stakeholders in the MBU and our hospital’s EMR analysts. Objectives: Assessing physician note optimization on saving time for patient care and improving provider satisfaction. Methods: This quality improvement pilot investigation was conducted in our MBU where four note templates were optimized: History and Physical (H&P), Progress Note (PN), Discharge Summary (DCS), and Hand-Off List (HOL). Free text elements documented elsewhere in the EMR (e.g. delivery information, maternal data, lab result, etc.) were identified and replaced with dynamic links that automatically populate the note with this data. Discrete data pick lists replaced necessary elements that were previously free text. The new note templates were given new names to ease accessibility. Ten randomly chosen pediatric residents completed both the old and the new note templates for the same control newborn encounter during a period of one year. Time spent and number of actions taken (clicks, keystrokes, transitions and mouse-keyboard switches) to complete these notes were recorded. Surveys were sent to the MBU providers regarding the overall satisfaction with the new note templates. Results: The ten residents’ average time saved was 23 minutes per infant. Reflecting this saved time on the number of infants admitted to our MBU between 1/2016-9/2019 which was 9373 infants; resulted in 2.6 hours saved per day, knowing that every infant averages two days length of stay. The new note templates required 69 fewer actions taken than the old ones (H&P: 11, PN: 8, DCS: 18, HOL: 32). The provider surveys were consistent with improved provider satisfaction. Conclusion: Optimizing physician notes saved time for patient care and improved physician satisfaction.